THINK SMART, THINK SOCIAL! THE ROAD MAP FROM SMARTER OBJECTS TO SOCIAL OBJECTS IN SOCIAL INTERNET OF THINGS - A SURVEY - Kowshalya, A. Meena; M.L, Valarmathi (Journal of Applied Engineering Science, 2017)
Internet of Things, the one paradigm many vision idea is ruling the world. By 2025 over trillions and trillions of objects will be connected to the internet. Social networking concepts are revolutions beyond IoT. One of the many visions of IoT is to make objects not only smarter but also socially conscious. A new paradigm named Social Internet of Things evolved which integrated two technologies namely Internet of Things and Social Networking. A SIoT comprises of socially aware smart objects that can autonomously establish and enable collaboration with other smart objects that are friends. In this paper we study the role, characteristics of social objects and their relationships. Five kinds of relationships are identified. These relationship and characteristics helps in revealing the level of trust between objects. Experiments were conducted for 85 social objects in an office environment and the types of objects, their relationships, interest, activities etc were discovered.